Pengaruh Jumlah Gigi Tarik Belakang Sepeda Motor Terhadap Konsumsi Bahan Bakar Pada Mesin 110 cc - MUNTHE, IMMANUEL (Journal of Engineering and Information Technology for Community Service, 2024)
In operation, the sprocket component always rubs against the chain of the motorcycle. The friction of the two components results in friction to transfer power to the rear wheel. In this study, the object of research is the Revo 110 cc Motorcycle sprocket. The purpose of this research is to get an analysis of the fuel consumption that occurs in the roller chain sprocket component of a motorcycle. In this study, 2 methods were carried out, namely literature and experiments. This research was conducted by testing and comparing three sprockets of 30, 37, 45 in the position of a standardized motorcycle without load with the same speed of 3000 rpm and the same test time for 1 hour. From comparing the three sprockets in terms of diameter and number of teeth and other parameters, it can be seen that the lowest fuel consumption is in gear 30, while the increasing number of sprocket teeth results in an increase in fuel consumption.